The Maisons Jaoul’s ceramic vaults: authenticity and technical tradition - Martín-García, Estefanía (Revista de Arquitectura, 2023)
The Maisons Jaoul were erected between 1954 and 1956 at a time of technological boom in reinforced concrete construction. These houses moved away from tectonic purism and from the Le Corbusier’s five architectural points, proposing a new-old machine for living, with various techniques and abandoning the cartesian planes and whit houses. The lowered barrel vaults, the load-bearing walls and the exposure of the materials caused disagreement among critics of the modern genius, who considered the Jaoul a regionalist experiment. This paper studies the technical and theoretical criteria of the houses through the analysis of the techniques and previous works of the architect. It will find a response to the structural steel tie bar of the Jaoul vaults through the interpretation of the sketches, plans and calculations made by Le Corbusier. The conclusions will highlight the importance of the constructive design, the changes during the project process and the built reality.